Grado de satisfacción en clientes de La Empresa Pública Emsaba. - Rivera Ramírez, Kevin Alexander (2022)
The public company Emsaba de Babahoyo, through an investigation and analysis, determines that this very important institution for the city has a series of very important shortcomings and administrative deficits that have been detected, this establishment does not maintain constant training. of its administrative and customer service staff, this being a very important factor, since in this aspect the staff does not know how to handle the situations that arise with the users, emphasizing that this problem is not major but considerable, it also presents problems in handling billing and collections due to poor meter readings, as well as multiple complaints due to the lack of rapid response from its technical operating staff.